Gas–Liquid Mixability Study in a Jet-Stirred Tank for Mineral Flotation - Yehao Huang; Mingwei Gao; Baozhong Shang; Jia Yao; Weijun Peng; Xiangyu Song; Dan Mei (Applied Sciences)
Micro- and nano-bubble jet stirring, as an emerging technology, shows great potential in complex mineral sorting. Flow field characteristics and structural parameters of the gas–liquid two-phase system can lead to uneven bubble distribution inside the reaction vessel. Gas–liquid mixing uniformity is crucial for evaluating stirring effects, as increasing the contact area enhances reaction efficiency. To improve flotation process efficiency and resource recovery, further investigation into flow field characteristics and structural optimization is necessary. The internal flow field of the jet-stirred tank was analyzed using computational fluid dynamics (CFDs) with the Eulerian multiphase flow model and the Renormalization Group (RNG) k − ε turbulence model. Various operating (feeding and aerating volumes) and structural parameters (nozzle direction, height, inner diameter, and radius ratio) were simulated. Dimensionless variance is a statistical metric used to assess gas–liquid mixing uniformity. The results indicated bubbles accumulated in the middle of the vessel, leading to uneven mixing. Lower velocities resulted in low gas volume fractions, while excessively high velocities increased differences between the center and near-wall regions. Optimal mixing uniformity was achieved with a circumferential nozzle direction, 80 mm height, 5.0 mm inner diameter, and 0.55 radius ratio.